New Formulation of Equitable Agricultural Profit - Lamase, Muh. Fadhir A.I.; Purwanti, Lilik; Mulawarman, Aji Dedi (The International Journal of Accounting and Business Society, 2026)
Purpose — This study aims to uncover the complexities of sugarcane farming in Jombang through a holistic approach. Its primary focus is to explore the cultural values and religious beliefs of farmers in order to redesign a more equitable and just concept of agricultural profit. Method — This study employs a qualitative method using the Nusantara Participatory Approach (NPA). Primary data were collected through in-depth interviews and participatory observation with sugarcane farmers and relevant agencies in Jombang, supplemented by secondary data from relevant literature to strengthen the analysis of the phenomenon. Result — The research findings reveal systemic inequities in the milling process, a lack of transparency in crop yield calculations, and a cycle of dependence on middlemen. Additionally, sugar import policies have been identified as an external factor undermining local price stability. The reconceptualization of agricultural profit in this study emphasizes that Net Farm Income (NFI) should not be viewed merely as a financial metric but should be integrated with social and religious values as the foundation for sustainability. Implication — Both practically and theoretically, this study provides a foundation for reforming profit formula policies in agricultural accounting to make them more humane and equitable for the agribusiness ecosystem in Indonesia. This study has significant implications for reforms to agricultural profit formulas and policies in both national and accounting contexts. The novelty of this study lies in the use of the Nusantara Participatory Approach (NPA) to redesign a more equitable and inclusive concept of agricultural profit. Originality — The novelty of this study lies in integrating local wisdom through the NPA approach to deconstruct and redesign the concept of agricultural profit, which has traditionally been rigidly bound by conventional accounting standards.